Public Health Implications of Household Pharmaceutical Waste in the United States - Kevin T. Bain (SAGE Publishing, 2010)
Household pharmaceuticals are ubiquitous and untold quantities are wasted annually. Most often, people dispose of household pharmaceuticals by flushing them down the toilet, pouring them down the drain, or throwing them away in the trash. Pharmaceuticals disposed in this manner compromise the safety of our environment. This article provides a comprehensive review on the public health issue of household pharmaceutical waste, describing its epidemiology, explaining its effects on aquatic and human life, estimating its cost burden, and discussing strategies for reducing environmental exposure to it. In doing so, this article proposes two key objectives for our nation: (1) reduce the amount of household pharmaceuticals wasted and (2) devise environmentally friendly and cost-effective ways for handling this waste once it has been generated.